The Effect Of Chief Executive Officer (CEO) Charcteristics And Earnings Management In Avoiding Losses: Evidence From Indonesia For The 2017-2022 Period - Shofaa Dhiyaa Urrahmani; Isnawati Isnawati (Cita Konsultindo Research Center, 2024)
This study investigates the effect of Chief Executive Officer (CEO) type on earnings management in avoiding losses in banking companies in Indonesia for the period 2017-2022. CEO type is divided into Founder CEO and Non-Founder CEO. Earnings management is measured through accrual earnings management and real earnings management. The sample consisted of 38 banking companies with 266 company-year observations. The results showed that CEO type has no significant effect on loss aversion or earnings decline. However, real earnings management and accrual earnings management have a significant effect on loss aversion or earnings decline. This finding indicates that banking companies in Indonesia tend to perform earnings management through real and accrual activities to avoid reporting losses or decreasing profits, but the practice is not influenced by the type of CEO. This study suggests the need for increased supervision and corporate governance to reduce earnings management practices